DIRECTIONS OF THE DIVERSIFICATION OF NATIONAL PRODUCTION - Saydaliyeva Lazizakhon (Journals Park Publishing, 2023)
The diversification of national production refers to the process by which a country expands and broadens its economic activities across multiple sectors and industries. This strategic approach aims to reduce reliance on a single industry or sector, enhance economic resilience, and stimulate overall growth and development. This scientific article is devoted to analyses of the directions of the diversification of national production. Moreover, the topic of the article is explained on the example Germany.
Keywords: economy, finance, macroeconomy, stabilizing the commercial banks, national production diversification.